INFLUENCE OF SETT SIZE, SEED RATE AND SETT TREATMENT ON YIELD AND QUALITY OF SUGARCANE - PATEL, DARPANA; PATEL, RINKU (The Bioscan, 2013)
A field experiment was conducted at Regional Sugarcane Research Station, Navsari, Gujarat (India) during 200809 to 2010-11 to study the influence of sett size, seed rate and sett treatment on yield, of sugarcane. The results of the experiment indicated that, planting of sugarcane with two bud sett found significantly superior in increasing number of millable canes (110250 ha-1), cane yield (110.42 t ha-1) as compared to three and single bud setts during all the three years of experimentation. The increase in cane yield was 6.86 % and 25.72 % in three and two bed setts respectively over single bud sett. Normal seed rate of 100 % of recommended buds ha-1 increased the number of millable canes ha-1, cane yield (100.83 t ha-1) and commercial cane sugar (ccs) yield (12.53 t ha-1) significantly as compared to lower seed rate of 75 % of recommended buds ha-1. Significant differences in cane yield, ccs yield and juice quality parameters were not observed due to sett treatment either with carbendazim @ 0.1 % alone or along with gibberellic acid @ 100 ppm for 15 minutes.